Understanding the evolving treatment landscape of hidradenitis suppurativa: An analysis of All of Us - Aditya K. Gupta; Vasiliki Economopoulos; Paradi Mirmirani; Renata Magalhaes (PLoS ONE, 2025)
Background Hidradenitis suppurativa (HS) is a chronic skin condition with significant burden for affected patients. The development of new therapies in the last decade has brought hope for better patient outcomes, but understanding the use of these new drug classes is necessary to ensure patient access to care. Methods We analysed data from 2636 HS patients within NIH’s All of Us research program from June 2017 and October 1, 2023 to examine the likelihood of patients receiving certain classes of drugs based on socio-demographic factors and comorbid health conditions, as well as how these drug classes impact quality of life. We also examined trends in the number of prescriptions over time. Results Antibiotics were most frequently prescribed, with higher numbers administered to females. Small molecule inhibitors and biologic medications were prescribed at low levels. We found that socio-demographic factors such as ethnicity, income and insurance provider influence the types of drugs patients are most likely to receive, with African American individuals more likely to receive antibiotics and immunosuppressive drugs and less likely to receive small molecule inhibitors. We also found that comorbid conditions significantly influence the likelihood of patients receiving specific drugs, with higher odds of receiving biologics if a patient has a comorbid rheumatic/autoimmune disorder. Antibiotics and immunosuppressive drugs were associated with less favourable quality of life measures, as well as a higher likelihood of anxiety and depression. Conclusions This work uncovers the varied landscape of HS treatment in the US and highlights the factors that influence treatment choices and how these treatments impact quality of life. It also provides an understanding of the social disparities that some populations face when accessing HS care, informing future decisions and practices to reduce these inequities.